When Achievement Meets Social Pressure: The Relationship Between Self-Enhancement and Self-Presentation Concerns Among MAN IC Students - Nia Kurniati; Subhan Ajrin Sudirman; Indah Andika Octavia; Rahman Pranovri Putra (Journal of Psychology and Instruction, 2025)
A competitive environment such as the MAN Insan Cendekia Padang Pariaman environment allows students to strive to display a positive self-image to meet social and academic expectations. This situation can be said that students are trying to improve themselves which is called self-enhancement. But this drive can also raise self- presentation concerns, especially in an effort to balance personal achievement and social expectations. This study aims to see the relationship between self -enhancement and self-presentation concerns in students. This study uses a quantitative research method with a correlational type. The total population in this study is 336 students with a sample of 240 students. The sampling technique in this study uses purposive sampling and data collection using a Likert scale model. The data collection in this study uses a scale of self-enhancement and self-presentation concerns. The results of this study show that the level of self-enhancement categorization is at a high level of categorization with a percentage of 60% and the categorization of self-presentation concerns is at a medium level of categorization with a percentage of 77.9%. This means that MAN Insan Cendekia Padang Pariaman students have an interest in advancing and defending themselves from negative views of themselves and others, so that MAN Insan Cendekia Padang Pariaman students do not depend on the judgment of others to advance, but the judgment of others is used as a means of self- improvement and improvement in the future. The results of this study also showed that self-enhancement was significantly negatively related to self-presentation concerns which referred to a significance value of 0.001 (p 0.005) with a negative correlation direction based on a correlation coefficient of r -0.592.